2019
DOI: 10.1097/pcc.0000000000002006
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breathing Trial for Prediction of Extubation Success in Pediatric Patients Following Congenital Heart Surgery: A Randomized Controlled Trial*

Abstract: Objectives: To evaluate the usefulness of a spontaneous breathing trial for predicting extubation success in pediatric patients in the postoperative period after cardiac surgery compared with a physician-led weaning. Study Design: Randomized, controlled trial. Setting: PICU of a tertiary-care university hospital. Patients: A population of pediatric patients follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
0
23
1
1
Order By: Relevance
“…However, for patients with congenital heart disease, spontaneous breathing trials and daily extubation readiness tests proved effective in reducing extubation failure and length of PICU-stay ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, for patients with congenital heart disease, spontaneous breathing trials and daily extubation readiness tests proved effective in reducing extubation failure and length of PICU-stay ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Together, these factors may have mitigated the beneficial effect shown in smaller paediatric explanatory trials evaluating a SBT as a weaning intervention. 22,71,72 Given the small number of paediatric trials that have evaluated SBT as a weaning strategy, it is no surprise that there are discordant results reporting duration of IMV across studies. In a two-centre RCT recruiting mainly medical patients, Foronda et al 22 reported a reduction in the duration of IMV of > 24 hours in the SBT group (n = 294, median 3.5 vs. 4.7 days; p = 0.01).…”
Section: Summary Of the Health Economic Analysismentioning
confidence: 99%
“…Se recomiendan las pruebas de respiración espontánea para ayudar a seleccionar al grupo de pacientes que se benefician de una extubación. Los pacientes sometidos a pruebas de respiración espontánea tienen mayor éxito en la extubación comparados con aquellos a los que no se les realiza (83% frente al 68%, p = 0,02) y tienen estancias más cortas en la unidad de cuidado intensivo pediátrico (mediana 85, frente a 367 horas, p <0,0001) (34). La finalización satisfactoria de una prueba de respiración podría predecir una extubación satisfactoria con una sensibilidad del 95%, con un valor predictivo positivo del 92% y una razón de posibilidades de 12 (IC 95%, 1,3 -53,7).…”
Section: ¿Cuál Es La Pauta Más Recomendada Para Preparar Un Paciente ...unclassified